Mesenchymal stem cells prolong the survival of orthotopic liver transplants by regulating the expression of TGF-β1 - Niu, Jian; Wang, Yue; Liu, Bin; Yao, Yuanhu (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Recent studies have shown that transforming growth factor-β1 (TGF-β1) is prominently associated with acute rejection. This study aimed to explore the role of mesenchymal stem cells (MSCs) in the maintenance of the long-term survival of orthotopic liver transplants (OLTs) via the regulation of TGF-β1 in an experimental rat model. Materials and Methods: We used Lewis rats as donors and ACI rats as recipients. Hematoxylin and eosin staining was performed to evaluate histomorphological changes, and Western blot was performed to measure protein expression. Results: The expression of TGF-β1 in the liver allografts and spleen and protein levels of forkhead box P3 (FoxP3), interleukin-10 (IL-10), and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) were measured using Western blot. The suppressive capacity of CD4+CD25+ regulatory T cells was evaluated using the MTT assay. Cell-mediated immunotoxicity was evaluated using the mixed lymphocyte reaction of CD4+ T cells and cytotoxic T lymphocyte (CTL) assay of CD8+ T cells. The results showed that MSCs prolonged the survival of the OLT mice by regulating the expression of TGF-β1 at different time points. The administration of MSCs promoted a prolonged survival in the ACI recipients (105±6.6 d) compared with the MSC-untreated recipients (16.2±4.0 d). On the postoperative day (POD) 7, the MSC-treated recipients showed a significantly higher expression of TGF-β1, FoxP3, IL-10, and CTLA-4 than the MSC-untreated recipients. However, on POD 100, the MSC-treated recipients showed a lower expression of TGF-β1 and FOxP3 than that on POD 7. Moreover, on POD 7, CD4+CD25+ regulatory T cells extracted from the MSC-treated recipients showed a higher expression of FoxP3, IL-10, CTLA-4, and suppressive capacity. On POD 7, CD4+ T cells from the MSC-treated recipients showed more significantly diminished proliferative functions than the MSC-untreated recipients; further, a reduced allospecific CTL activity of CD8+ T cells was observed in the MSC-treated recipients. Conclusion: MSCs may represent a promising cell therapeutic approach for inducing immunosuppression or transplant tolerance. Cite this article as: Niu J, Wang Y, Liu B, Yao Y. Mesenchymal stem cells prolong the survival of orthotopic liver transplants by regulating the expression of TGF-β1. Turk J Gastroenterol 2018; 29: 601-9.